CARD (Coalition for African Rice Development) initiative has contributed to increase rice production by 10.2 million ton in 2018, benefiting both rice producers and consumers - CGIAR Research Program on Rice (2021)
Following the food price crisis in 2008, African governments, with support of partners including AfricaRice, JICA, etc., implemented policies through the Coalition for African Rice Development (CARD) to double rice production by 2018. We assessed the contribution of the CARD policy to rice production: the CARD policy contributed to increased rice production in 2018 by 10.2 million ton, which benefited both rice producers (increased sales and income) and rice consumers (lower market prices than without rice production increase).